ANALISIS KUALITAS PELAYANAN LEMBAGA PELATIHAN KURSUS KOMPUTER UNTUK MENINGKATKAN KEPUASAN SISWA PADA PONDOK PESANTREN DARUL HIJRAH PUTRA CINDAI ALUS MARTAPURA - jaya bahwiyanti yaya; Rama Andri Syawalli Rama Andri Syawalli (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
Abstract: The purpose of this study was to determine the level of satisfaction in first grade junior high school students at the Martapura Darul Hijrah Islamic Boarding School which was seen from the service quality factors which involved physical / tangible evidence, reliability, responsiveness, Assurance and Empathy.The research method used is descriptive quantitative type by discussing a study with numbers. Figures obtained from a questionnaire were distributed to 100 students and later the percentage index will be calculated to determine the level of satisfaction of service quality variables. The results showed that all the quality variables of LPK-AL-Hijrah service received a Satisfied Enough value by students who obtained the Percentage Index result with an interpretation distance of 20% from the 5 choice categories was 48.31%.